Investigation of the Effect of Using Surgical Face Masks on Aerobic and Anaerobic Performance of Children During Educational Games - Mehmet Şerif Ökmen, Yaşar Köroğlu, Mehmet Sarikaya (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study aimed to examine the effect of participating in educational game activities with and without a surgical face mask on the aerobic and anaerobic performance levels ​​of children aged 12-13. Methods: Two male groups, unmasked (n=22) and masked (n=22), participated in the study. Pre-test post-test experimental model was used in the study. The aerobic performances of the groups were determined by the 20m shuttle test, and the anaerobic performances of the groups were determined by the vertical jump test. After the pretest scores ​​of the groups were taken, educational game activities were applied to both groups three days a week for eight weeks. At the end of the eighth week, post-test scores were obtained. These data were presented as arithmetic mean and standard deviation. Independent sample t test was used to compare independent groups and paired sample t test was used to compare dependent groups. Results: Significance level was set as p<0.05. When the pretest and posttest values of age, height and body weight ​​of the groups were compared between the groups, no significant difference was observed (p<0.005). However, when looked at the in-group scores, it was observed that there was a significant difference in the body weight values ​​of the masked group (p˂0.001). In addition, there was a significant difference between the pretest and posttest aerobic performance (MaxVO2) scores ​​of both groups within the group comparison (p˂0.001), but no significant difference was found in the groups’ anaerobic performance scores (p<0.005). However, there was no significant difference between the pretest scores ​​between the groups, while a significant difference was observed between the post-test aerobic (p˂0.001) and anaerobic (p<0.005) scores. Conclusion: As a result, children’s participation in regular educational games activities both with and without masks contributes positively to their aerobic performance and it can be said that the aerobic (16.69%) and anaerobic (1.01%) performance scores percentages of the masked group improved more than the unmasked group.